Is Human Trafficking's Victim Receive Zakat as Riqab?: Zakat Distribution at East Java Philanthropic Organizations - Ibadi, Nur; Hardi, Eja Armaz (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This paper aims to analyze human trafficking victims in the zakat distribution discourse in six philanthropic institutions in East Java and to describe the supporting and inhibiting factors in determining human trafficking victims as riqab. Human trafficking victims have not been touched by the zakat system in Indonesia, while the number of victims has simultaneously increased. This paper utilizes a field study that uses primary data from in-depth interviews with top leaders of six zakat institutions under the National Amil Zakat Agency. In addition, this paper also uses secondary data sourced from documentation and annual reports released by the research object. This paper concludes that, firstly, victims of human trafficking have met the criteria to be zakat recipients on behalf of riqab. Although in practice in the field, no East Java zakat institution distributes zakat to victims of human trafficking. Second, East Java zakat institutions have the potential for proportional support to distribute zakat in the name of riqab to victims of human trafficking. Its implementation still encounters obstacles but can be overcome with the current potential.